Comunicación alternativa en época de pandemia a los estudiantes de la Unidad Educativa Daule Peripa del cantón El Empalme - Zambrano Chávez, Nathali Marbel (2021)
For the development of this project, analytical, statistical, descriptive, field methods and techniques will be used, investigating the benefits of alternative communication, considering if all the students of the Daule Peripa Educational Unit can access it, what have been the main obstacles, in its use, and if they have had to resort to other types of sources for their training. The learning options are multiple through alternative communication, they allow to be connected to share, participate and integrate new members regardless of their political, social, economic or physical conditions, which influences that the student is no longer just a receiving entity and that you can now intrude as an active member of the classroom challenging your teachers in the field of knowledge. At present, thanks to technology and its eminent development, there is a new era of alternative communication where each citizen can express his point of view freely on political, economic, social and educational issues that involve the population, the student as well as an element of society where you can know and be informed of all events and give your opinion without following traditional methods expanding your understanding.